2008
DOI: 10.1007/s10389-008-0211-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of gastrointestinal parasites among hospitalized patients attending Al-Nasser Paediatric Hospital, Gaza, Palestine

Abstract: Aims The aim of this study was to determine the prevalence of the diagnosed gastrointestinal parasites among hospitalized children attending the Al-Nasser Paediatric Hospital. Method This was a cross-sectional study among hospitalized children attending the Al-Nasser Paediatric Hospital. The study included 522 children during the period May 2002 to May 2003. Data collection included two methods: medical laboratory results for the examination of stool specimens and a questionnaire. Wet mount using saline and Lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…In accordance with our results, Perch et al., ​[47] and Gatei et al., ​[48] found that infection rates did not differ with gender distribution. However, some studies [49, 50, 51] showed variation with gender of statistical significance. Al Hindi et al., ​[49] found that the number of infected females was significantly higher than males, while, Park et al., ​[50] and Mumtaz et al., ​[51] declared higher prevalence rates in males.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance with our results, Perch et al., ​[47] and Gatei et al., ​[48] found that infection rates did not differ with gender distribution. However, some studies [49, 50, 51] showed variation with gender of statistical significance. Al Hindi et al., ​[49] found that the number of infected females was significantly higher than males, while, Park et al., ​[50] and Mumtaz et al., ​[51] declared higher prevalence rates in males.…”
Section: Discussionmentioning
confidence: 99%
“…However, some studies [49, 50, 51] showed variation with gender of statistical significance. Al Hindi et al., ​[49] found that the number of infected females was significantly higher than males, while, Park et al., ​[50] and Mumtaz et al., ​[51] declared higher prevalence rates in males.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal parasite incidence were reported by many studies in Gaza strip, including Giardia lamblia, Entamoeba histolytica/dispar, Ascaris lumbricoides, Trichuris trichiura, Enterobius vermicularis and Strongyloides stercoralis (Shubair et al 2000;AlHindi 2002). The prevalence rate of intestinal parasites in Palestine was ranged from 27.6-32.3 % in Gaza strip, and 22.2 % in West Bank, the most common types were Giardia lamnblia and Entamoeba histolytica/dispar (Shtayeh et al 1989;Yassin et al 1999;Al-Hindi, 2009;Hussein 2011;Al-Hindi and Al-Louh, 2013). The prevalence of E. vermicularis among preschool children in nursery setting in Gaza strip reached to 46.3 % .…”
Section: Introductionmentioning
confidence: 98%
“…Despite its wide distribution in the environment, there is very little awareness about this protozoan parasite and the poor laboratory techniques which are limited to direct smear in the local medical laboratories in hospitals and private laboratories in Jos could also have accounted for this low prevalence rate. Our study lower prevalence of 4.8% falls within the lower range of the 5-10% reported worldwide in the study by Vandenberg et al [ 27 ] and this may be attributed to our small sample size, and the differences in the age of our study population, environmental factors (water source, sanitary condition), study timing, children nutritional status, parents socioeconomic status, undiagnosed co-infection, microscopic methods amongst other risk factors, which we did not study [ 28 , 29 ].However, the disease transmission and other geographic features of Cryptosporidium infection among children in North-Central Nigeria are yet to be well investigated and this has contributed to paucity of data in population-based study. This study observed disproportionately high prevalence of Cryptosporidium infection among children aged 37-48 months (14.3%), and low (4.5%) in those aged 0-12 months.…”
Section: Discussionmentioning
confidence: 63%